ChemInform Abstract: Iron(III) Chloride‐Catalyzed Decarboxylative—Deaminative Functionalization of Phenylglycine: A Tandem Synthesis of Quinazolinones and Benzimidazoles. Issue 5 (January 2016) - Kumar, Manoranjan; Richa, Manoranjan; Sharma, Sushila; Bhatt, Vinod; Kumar, Neeraj
Abstract: A novel procedure is elaborated for the synthesis of quinazolinones (III) from 2‐nitrobenzonitriles (I) and phenylglycines (II).